Quantifying the factors affecting wood decomposition across a tropical forest disturbance gradient - Dossa, G.G.O.; Paudel, E.; Schaefer, D.; Zhang, J.L.; Cao, K.-F.; Xu, J.C.; Harrison, R.D. (Elsevier, 2020)
Woody debris represents a substantial reservoir of carbon in forests. Disentangling the effects of factors affecting wood decomposition rates is therefore important. We examined the abiotic and biotic factors affecting wood decomposition across a disturbance gradient from mature forest to open land in a tropical montane site in Xishuangbanna, SW China. Wood logs (n = 280) of two native species with contrasting wood specific gravity (WSG), Castanopsis mekongensis (0.75) and Litsea cubeba (0.42), were exposed on the ground for three years. For each log, WSG was monitored at intervals by taking cores from top-half (up) and bottom-half (down) of the log. Mass loss was measured at the end of the experiment. WSG loss rates were similar across the disturbance gradient and the species effect varied with core position. For Castanopsis, which had higher initial WSG and wood N concentration and much thicker bark, up-cores had consistently higher WSG loss over the study period. This species also had substantially higher WSG loss for up-cores, but interspecific difference among down-cores was small. For mass loss, there was a complex interaction between species, habitat and the presence of termites. Litsea with low initial WSG experienced approximately two-fold higher mass loss in the absence of termites, but the difference between species was smaller in the presence of termites. Both species experienced higher mass loss in open habitats than in forests, but the termite effect was smaller in open habitats especially for Litsea. There was no interspecific difference in susceptibility to termite infestation, but infestation rates were higher in regenerating forests and open land than in mature forest. WSG loss explained 0% and 19% of mass loss variation in Listea and Castanopsis, respectively, in absence of termites and 0% for both in the presence of termites. Afterlife effects of wood functional traits interact with abiotic conditions and decomposition processes (microbial decomposition, macro-organisms (termites), photo-degradation) in a complex manner to determine wood decomposition rates. WSG loss is not a reliable predictor of mass loss. These results have important implications for understanding the carbon cycle in tropical landscapes that are undergoing anthropogenic disturbance.